Recovering Together: Mothers' Experiences Providing Skin-to-Skin Care for Their Infants With NAS. (February 2021) - McGlothen-Bell, Kelly; Recto, Pamela; McGrath, Jacqueline M.; Brownell, Elizabeth; Cleveland, Lisa M.
Abstract : Background: Over the past 2 decades, the prevalence of neonatal abstinence syndrome (NAS) has increased almost 5-fold. Skin-to-skin care (SSC), a method of parent–infant holding, is a recommended nonpharmacologic intervention for managing NAS symptoms. SSC has the potential to reduce withdrawal symptoms while positively influencing parent–infant attachment. Yet, little is known about the SSC experiences of mothers of infants with NAS. Purpose: The purpose of this study was to explore the SSC experiences of mothers of infants with NAS, including perceived barriers to SSC in the hospital and following discharge home. Methods: A qualitative descriptive design was used to obtain new knowledge regarding the experience of SSC of mothers of infants with NAS. Purposive sampling was used to recruit participants eligible for the study. We conducted semistructured individual interviews with postpartum mothers of infants with NAS. Data were analyzed using thematic analysis. Findings/Results: Thirteen mothers participated in the study. Four themes emerged from the data analysis: "a little nerve racking"; "she needed me, and I needed her"; dealing with the "hard times"; and "a piece of my puzzle is missing." SSC was described as a conduit for healing and bonding; in addition, several barriers to SSC were reported. Implications for Practice and Research: These findings highlight the inherent benefits of SSC for infants with NAS and demonstrate the unique challenges of these mother–infant dyads. Critical changes in hospital practices are needed to create an environment supportive of SSC for this patient population. In addition, research regarding implementation of interventions to increase SSC usage in this population is warranted.